Pengarug Gaya Kepemimpinan, Budaya Organisasi, dan Kepercayaan Pegawai terhadap Komitmen Organisasi pada Suku Dinas Pendidikan Dasar Kota Administrasi Jakarta Barat - Soeparlan Kasyadi (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2013)
This research is aimed at obtaining information related to the affect of the leadership style, organizational culture, and employees’ trust on organizational commitment. Research has been implemented using path analysis after all variables put into a matrix of correlation. In this research, employees had been chosen as a unit analysis and 65 samples selected randomly. The results of research found out that: (1) there is direct affect of leadership style on employees’ trust; (2) there is direct affect of organizational culture on employees’ trust; (3) there is direct affect of leadership style on organizational commitment; (4) there is direct affect of organizational culture on organizational commitment; and (5) there is direct affect of employees’ trust on organizational commitment. Based on those findings it could be concluded that any changing or variation which occurred to the organizational commitment of Basic Education Office in West Jakarta had been effected by leadership style, organizational culture, and trust to employees. Therefore, leadership style, organizational culture, and employees’ trust should be put into strategic planning of human resources development in increasing the organizational commitment of Basic Education Office in West Jakarta, however other variables are necessary to be taken into account properly.